The nature and sources of the emotional distress felt by intensivists and the burdens that are carried: A qualitative study. Issue 1 (January 2023) - Dennis, Diane; Vernon van Heerden, Peter; Knott, Cameron; Khanna, Rahul
Abstract: Background: Work in intensive care units is often traumatic and emotionally distressing, sometimes leading to growth but at other times to negative outcomes such as worker burnout and mental illness. The type and origin of distresses to intensivists has been poorly characterised in the literature. This evidence gap makes it difficult to develop tailored educational process or cultural interventions for all who work within the specialty. Objectives: The aim of this study was to elicit the nature and sources of workplace emotional distress in an international sample of intensivists. Method: Interviews were undertaken with experienced intensivists in Australia and Israel related to the basis of workplace distress. These were transcribed and qualitatively thematically analysed. Results: In 2018, 19 intensivists participated in the study. Several key themes emerged from data analysis, some relating to clinical work, such as catastrophic patient outcomes, and some relating to interpersonal and systems-level challenges. Navigating complex interpersonal dynamics with carers and staff, both within and outside the intensive care unit team, caused substantial emotional burden. Conclusions: Many factors contribute to workplace stress for doctors in the intensive care setting. In elucidating common reactions to these stressors, we have attempted to normalise responses. We further note that the skill sets relevant to the many challenges identified are generally missing in medical training curricula. It may be prudent to consider their inclusion in the future.